Altered luteal expression patterns of genomic and non-genomic progesterone receptors in bitches at different reproductive states - Ucar, Eyyup Hakan; Peker, Cevdet; Hitit, Mustafa; Kose, Mehmet; Tatar, Musa; Bozkaya, Faruk; Atli, Mehmet Osman (Elsevier BV, 2024)
The binding of steroid hormones to their specific receptors is necessary to exert their effects on target cells. Progesterone (P4), a steroid hormone, carries out its effects through both genomic and non-genomic (the cell membrane-associated) receptors. This study aimed to ascertain luteal expression patterns of genomic and non-genomic progesterone receptors in bitches in physiological (early dioestrus and early pregnant) and pathological (pyometra) reproductive states. Luteal tissue was collected from the bitches at early dioestrus (ED, n = 5), early pregnant (EP, n = 5), and pyometra (PY, n = 5). The expression profiles of Steroidogenic Acute Regulator Protein (STAR), Progesterone Receptor (PGR), Membrane Progestin Receptors (PAQR5, PAQR7 and PAQR8), and Progesterone Membrane Components (PGMRC1 and PGMRC2) were examined at the mRNA levels using Real-Time Polymerase Chain Reaction (RT-PCR). Protein levels of PGR, PGMRC1 and PGMRC2 were detected by western blotting (WB). The STAR expression was found in all groups, with a statistical difference observed between EP and PY groups (P < 0.05). The protein level of PGR was determined to be highest in the EP group and lowest in the PY group. The expression of PAQR8 increased in the EP group (P < 0.05). The PAQR5 exhibited high expression in the EP group and low expression in the PY group (P < 0.05). PGRMC1 was more elevated in the EP group and lower in the PY group (P < 0.05). Protein levels of PGMRC1 and PGMRC2 were also observed at the highest expression in EP group. According to the altered expression profiles for examined receptors, we suggest that those progesterone receptors have roles in early pregnancy or pyometra in bitches.
Keywords: Genomic and non-genomic progesterone receptors; Pregnancy; Pyometra; Lutein; Animals; Female; Genomics; Bitches; Receptors, Progesterone; Early pregnancy; Progesterone